Comparison of the Effectiveness of Transcutaneous Electrical Nerve Stimulation and Microcurrent Nerve Stimulation in Reducing Clinical Symptoms in Patients with Temporomandibular Joint Dysfunction - Proshchenko А. М.; Shynchukovskyi І. А. (Actual Dentistry, 2024)
Abstract. Today, the prevalence of temporomandibular joint dysfunction among the world’s population is approximately 80%. Quite often, this disease significantly impairs the quality of life, sometimes even leading to disability. Today, there are methods for treating temporomandibular joint dysfunction with electrotherapy, including transcutaneous electrical nerve. The study aimed to compare the effectiveness of TENS and MENS therapy in reducing clinical symptoms in patients with temporomandibular joint dysfunction. Materials and methods: 40 participants participated in the study and were randomly divided into 2 groups. Group I received treatment with TENS therapy, and group II—MENS therapy. The frequency of treatment was 2 sessions per week, and the total duration of treatment was 10 sessions. Results. In comparison, between the baseline and the result at the end of 10 sessions, the HRV in group I decreased by 37.5% and in group II —by 27.03%. When comparing the results of treatment for VAS between the baseline and 1 month after treatment, the results in group I showed a 33.33% reduction in pain, and in group II 22.98%. The improvement in maximum mouth opening at 10 sessions compared to the baseline in group I was 12.98% and in group II —10.67%. When comparing the indicators of maximum mouth opening between the baseline and one month after treatment, an increase in this parameter was observed in group I by 11.87% and in group II — by 9.43%. Conclusions: according to the study results, the use of TENS- and MENS therapy is effective in treating temporomandibular joint disorders, but during the treatment, TENS therapy showed slightly better results in reducing clinical symptoms. However, 1 month after the end of treatment, the effect of electrotherapy decreases slightly, but still, the clinical symptoms are better compared to the initial situation.